2000
DOI: 10.1002/(sici)1097-0207(20000310)47:7<1263::aid-nme811>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal transformations of the integration variables in computation of singular integrals in BEM

Abstract: SUMMARYThe paper deals with numerical integrations of singular integrals in BEMs. It is shown that from the point of view of numerical integrations, the only serious problem which can arise is due to weakly singular and nearly singular integrals. We pay attention to the study of numerical integrations of nearly singular integrals by using transformations of the integration variables. Theoretical considerations and numerical experiments are performed for the integrals occurring in 2-D BEM formulations. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Burton and Miller showed that the two integral equations share only one common solution and thus their combination will overcome the mathematical uniqueness difficulty [22]. However, the normal derivative integral equation contains a hyper-singular integral kernel which is numerically formidable (the integral does not exist because of divergent terms in the primitive function of the integrand [23]). A large body of literature exists on the regularisation and computation of these integrals, which remains a somewhat problematic task [24][25][26].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Burton and Miller showed that the two integral equations share only one common solution and thus their combination will overcome the mathematical uniqueness difficulty [22]. However, the normal derivative integral equation contains a hyper-singular integral kernel which is numerically formidable (the integral does not exist because of divergent terms in the primitive function of the integrand [23]). A large body of literature exists on the regularisation and computation of these integrals, which remains a somewhat problematic task [24][25][26].…”
Section: Article In Pressmentioning
confidence: 99%
“…This may be used in conjunction with Telles adaptive transform to adjust the optimisation parameter automatically. However, previous investigations have illustrated the strong sensitivity of the integration accuracy to the optimisation parameter [23], and recently other transformations suitable for computing nearly weakly singular integrals have also been proposed [54,55]. In particular, the sinh transformation by Johnston and Elliot provides a useful alternative [50,55,56].…”
Section: Computation Of Nearly Singular Integralsmentioning
confidence: 99%
“…Apart from pure analytical integration, which has obvious limitations (low order elements), many other methods have been devised. The methods developed so far include, but are not limited to, element subdivision methods [15][16][17], semi-analytical methods [6,18,19] and various nonlinear transformations [20][21][22][23][24][25][26][27]. The element subdivision method is appealing, stable, and accurate but is costly because the number of sub-elements and their sizes are strongly dependent on the order of the near singularity and the dimension of the element.…”
Section: Introductionmentioning
confidence: 99%
“…However, from the point of view of numerical integrations, these integrals can not be calculated accurately by using the conventional numerical quadrature since the integrand oscillates seriously within the integration interval. In the past decades, tremendous effort was devoted to derive convenient integral forms or sophisticated computational techniques for calculating the nearly singular integrals, such as the interval subdivision method [27,28], special Gaussian quadrature method [29] and various nonlinear transformation methods [30][31][32][33][34][35][36][37][38]. Among all the available methods, analytical integration as an alternative way to improve the calculation accuracy of the nearly singular integrals has received a great amount of attention.…”
Section: Introductionmentioning
confidence: 99%